Global civil society? - Keane, John, 1949- (Contemporary political theory., 2003)
Amid fears of terrorism, rising tides of xenophobia, and loose talk of 'anti-globalisation', John Keane mounts a defence of global civil society, stressing the need for new democratic ways of living. Keane's provocative reflections draw upon a variety of scholarly sources to breathe new life into contemporary political thinking.